Phosphonium-based ionic liquids and their application in separation of dye from aqueous solution - Ullah, Z. (Asian Research Publishing Network, 2016)
In this study, phosphonium-based hydrophobic ionic liquids were synthesized and confirm their structures by NMR, FT-IR and CHNS. Their thermal stability was studied by thermo gravimetric analysis (TGA) and shows excellent thermal stability as compare to other ILs. Comparatively phosphonium-based ILs are less elaborated for many applications. Although in separation technology the ILs applications are still in their early stages, the academic interest is increasing in ILs. Dyes are the substantial source of pollution as a wastewater. These ILs were applied as adsorbent for the removal of methylene blue (MB) dye from aqueous media and the selected IL on laboratory scale shows good performance with the stripping efficiency of 84.95. The kinetics study expressed that the adsorption of MB on ILfitted in the pseudo-second order kinetics models with correlation coefficient value (R2) of 0.999. The study proved that ionic liquids are an effective and environmentally benign adsorbent for MB removal from aqueous solution. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.